2008
DOI: 10.1007/s10620-008-0485-6
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Symptoms and Associated Disorders in Morbidly Obese Patients: A Prospective Study

Abstract: These observations suggest a significant increase in the frequency of heartburn, hiatal hernia, and histologically identified gastritis in morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 20 publications
2
41
1
2
Order By: Relevance
“…Dutta et al (11) found prevalence of gastric ulcer of 2.9%, identified histologically gastritis in 23.7% and H. pylori in 6.9% in the obese patients, finding that was not different from the control (non-obese) patients.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Dutta et al (11) found prevalence of gastric ulcer of 2.9%, identified histologically gastritis in 23.7% and H. pylori in 6.9% in the obese patients, finding that was not different from the control (non-obese) patients.…”
Section: Discussionmentioning
confidence: 86%
“…Eradication of the H. pylori as a routine in the preoperative of bariatric surgery is still debated and scarce researches were performed in regards the histology of gastric mucosa (2,7,11,23,25,26,30,33,34,35) . Mong et al (25) studied 272 patients who were candidates to bariatric surgery, in which 33 (12%) showed lesions in the upper digestive tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Dutta et al, it was observed that reflux symptoms, endoscopically and histologically detected gastritis, and endoscopically detected hiatal hernia were more frequent in morbidly obese patients [8]. In two different studies by Pandolfino et al and Lee et al, it was reported that increased intragastric pressure and gastroesophageal pressure gradients increased the risk of hiatal hernia in direct proportion to increased BMI [13,14].…”
Section: Discussionmentioning
confidence: 98%
“…Obesity is also an independent risk factor for gastroesophageal reflux disease. Obesity not only leads to susceptibility to gastroesophageal reflux disease but also is itself an important independent risk factor for the development of hiatal hernia [4][5][6][7][8]. A coexisting hiatal hernia is found in half of obese patients with gastroesophageal reflux disease symptoms.…”
Section: Introductionmentioning
confidence: 99%